A patient with spontaneous bilateral renal vein thrombosis but no risk factors. (March 2023) - Pradhan, Jigyasha; Han, Shiwei; Girishkumar, Hanasoge
Abstract: Introduction and importance: Spontaneous bilateral renal vein thrombosis is a rare condition, especially when the patient has no risk factors. Case presentation: In this report, we describe a patient with bilateral renal vein thrombosis who presented with severe flank pain, renal functions remained normal, and the thrombus resolved completely with anticoagulation. There is no history of hypercoagulable condition in our patient. A one-year followup with CT angiogram revealed that the kidney was functioning normally and that the thrombus in the renal veins had completely resolved. Clinical discussion: Management of an acute renal vein thrombosis depends upon whether the patient presents with acute kidney injury. In general, patients without acute kidney injury can be treated with therapeutic anticoagulation, whereas those with acute kidney injury should undergo dissolution or removal of the thrombus with thrombolytic therapy with or without thrombectomy. Conclusion: Diagnosis of spontaneous renal vein thrombosis requires a high index of suspicion. Patient can be managed with therapeutic anticoagulation if renal function is intact. If thrombolysis and/or thrombectomy are performed on time, kidney function can be fully restored. Highlights: Spontaneous bilateral renal vein thrombosis is a rare condition, especially when the patient has no risk factors. If a patient presents with abdominal pain, flank pain, AKI and dehydration, renal vein thrombosis should be suspected. Patient with bilateral RVT can be managed with therapeutic anticoagulation if renal function is intact. If thrombolysis is performed on time, kidney function can be fully restored.